PERENCANAAN SISTEM TATA UDARA RUANG OPERASI DI RUMAH SAKIT IBU DAN ANAK PURI BUNDA TABANAN BALI - Kade Suwiherawan, I Gusti Ngurah; Dyana Arjana, I Gede; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p33, 2021)
The Puri Bunda Mother and Child Hospital in Denpasar opened a new branch in Tabanan. The operating room is one of the focuses in realizing patient safety-oriented services. The government with PMK No. 24 of 2016 and Technical Guidelines for Hospital Infrastructure for Air System Installation Systems in 2012 requires operating rooms to meet requirements such as: room temperature ranges from 20ºC - 24ºC, humidity 40% - 60%, equipped with HEPA filter with 99.97% efficiency, positive pressure of 15 pascal to the surrounding space, and equipped with a clean air exchange system. the result research and calculations in planning the operating room air conditioning system at the Puri Bunda Tabanan Mother and Child Hospital according to the standards obtained a split duct capacity of 60,000 btu / h, a heater of 7KW, a Booster fan of 1900 CFM, a HEPA filter of 120cm x 80cm. 2 units for each room, 42cm x 42cm ducting inlet outlet, 20cm x 25cm RAG and FAG ducting, 380 CFM exhaust fan.